SOME ASPECTS OF TEACHING FOREIGN STUDENTS RUSSIAN PRONUNCIATION - M. Sh. Boltaeva (Bright Mind Publishing, 2025)
This article examines the main aspects that should be considered when teaching foreign students Russian pronunciation, as well as proposes effective methods and approaches. It discusses important issues related to Russian pronunciation at the initial stage of learning for foreign students, as well as the development and improvement of their auditory and pronunciation skills. The necessity of mastering listening skills is emphasized. Teaching Russian pronunciation is an essential part of language acquisition for foreign students, especially if their primary field of study is not philology.
Keywords: Main aspects, foreign students, Russian pronunciation, effective methodologies and approaches, improvement, auditory-pronunciation skills, Russian language proficiency.